1993
DOI: 10.1007/bf01204444
|View full text |Cite
|
Sign up to set email alerts
|

Complications of transvaginal ultrasound-directed follicle aspiration: A review of 2670 consecutive procedures

Abstract: The low incidence of pelvic infection questions the value of using prophylactic antibiotics. No increased risk of infection was demonstrated in cases with preexisting peritoneal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
102
0
8

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(110 citation statements)
references
References 10 publications
0
102
0
8
Order By: Relevance
“…This paper reports 10 cases of PID following oocyte pickup with the suggestion of endometriosis as a potential risk factor. Inoculation of vaginal bacteria and anaerobe opportunists is suggested to be the cause of PID following oocyte retrieval (Bennett et al, 1993). Microorganisms of vagina are suggested to be the etiological pathogens in pelvic abscesses when transvaginal oocyte retrieval is used (Bennett et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This paper reports 10 cases of PID following oocyte pickup with the suggestion of endometriosis as a potential risk factor. Inoculation of vaginal bacteria and anaerobe opportunists is suggested to be the cause of PID following oocyte retrieval (Bennett et al, 1993). Microorganisms of vagina are suggested to be the etiological pathogens in pelvic abscesses when transvaginal oocyte retrieval is used (Bennett et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Egbase et al [23] reported that prophylactic antibiotics at TV-OPU, not only reduced the number of microbiology positive embryo catheter tips 48 h after the procedure, but also significantly increased implantation and clinical pregnancy rates. The pelvic infection rate was between 0.4 and 0.6 % in some studies where routine antibiotics prophylaxis was not administered [4,6]. Prophylaxis has been strongly advocated by some authors [24], but substantial evidence for its usefulness seems to be lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Though Serour et al [16] recommend the routine use of color Doppler at TV-OPU, Risquez and Confino [17] advice that the identification of smaller blood vessels on ultrasound Doppler may not entirely remove the risk of moderate to severe bleeding. Shalev et al [15] recommend the use of a pelvic ultrasound scan before discharging the women from the unit to Iatrogenic pelvic infection following TV-OPU can occur as a result of ascending infection (follicular aspiration needle carrying micro-organisms from the vagina into the pelvis), by the reactivation of a dormant infection (from a previous PID) or very unlikely, from fecal peritonitis secondary to bowel injury [6]. Pelvic infections occur within a few days to couple of weeks' of the procedure, but delayed pelvic infection in early pregnancy and in late pregnancy has also been reported [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with prophylactic antibiotics, the reported incidence of pelvic infection in OCR was around 0.6% (2). So far, there is no effective method of preventing this undesired complication.…”
Section: Introductionmentioning
confidence: 99%